Adaptive reused bangunan cagar budaya berbasis arsitektur berkelanjutan - Triratma, Bambang; Yuliani, Sri; Sofyan, Yuan Efano; Basith, Assyafa'ul (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Selective reuse of heritage buildings should be based on consideration of strategic issues of sustainable development. Research that discusses the reuse of cultural heritage buildings in the field of architecture still does not implement the concept of sustainable architecture. The purpose of the study is to obtain a strategy formulation that can be used as a parameter for adaptive implementation of reuse in cultural heritage buildings in line with sustainable development. The research took a case study of De Tjolomadoe building in Surakarta City, Indonesia. The building is a former sugar factory building currently converted as a meeting place, tourist destination, and educational communal space. The benefits of the research provide recommendations for adaptive reused strategies for cultural heritage buildings with the concept of sustainable architecture to support sustainable development. The study used in-depth observation with interview techniques and secondary data from the literature as the determination of the most important factor of the concept of sustainable architecture in optimizing the management of cultural heritage buildings. The results show that there are four architectural aspects that need to be considered so that adaptive reused cultural heritage buildings can provide sustainable benefits, i.e., the need for integration and synergy between building history, culture, environment.